PENGEMBANGAN MEDIA AJAR BERBASIS MULTIMEDIA AUDIO VISUAL PADA POKOK BAHASAN TEKANAN DI SMP - Galeh Aji Wardoyo; Syubhan Annur; Abdul Salam M (Universitas Lambung Mangkurat, 2017)
Low student learning outcomes of students allegedly did not follow the learning process because the media used is not attractive, so it is necessary to study development aimed at generating media-based teaching with audio-visual multimedia on the subject of pressure. The specific objective of research is to explain: (1) the validity of teaching media, (2) the practicality of teaching media views of enforceability to the lesson plan, (3) the effectiveness of teaching media. This study refers to the model ADDIE (Analysis Design, Development, Implement, and Evaluate). Data collection techniques such as teaching media validation, observation enforceability of the lesson plan, and achievement test. Data analysis techniques in the form of qualitative and quantitative descriptive. The results showed: (1) the validity of teaching media rated on validation by two validator with excellent category, (2) the practicality of teaching media rated executed very well, (3) the effectiveness of teaching media is considered effective. Be concluded that the teaching media based multimedia developed eligible for use in learning.